Analysis of the Sports Psychological Profile, Competitive Anxiety, Self-Confidence and Flow State in Young Football Players - José A. Domínguez-González; Rafael E. Reigal; Verónica Morales-Sánchez; Antonio Hernández-Mendo (MDPI AG, 2024)
The objective of this study was to analyse the correlations among the sports psychological profile, competitive anxiety, self-confidence and the flow state of young football players. Additionally, potential distinctions based on age category, competitive level and field position were explored. This study included 328 participants divided into two groups: Group 1, 14-15 year olds, and Group 2, 16-18 year olds (M = 15.85; SD = 1.44). Data were collected by using the Psychological Inventory of Sports Execution (IPED), the Revised Competitive State Anxiety Inventory-2 (CSAI-2R) and the Flow State Scale (FSS). The findings revealed positive associations between the sports psychological profile and self-confidence, as well as with the flow state. Conversely, competitive anxiety demonstrated negative relationships with the sports psychological profile, self-confidence and the state of flow. Moreover, superior scores were observed in the analysed variables for the older age category and higher competitive level, with no notable disparities based on field positions. These results underscore the interplay of psychological factors in the performance of football players and underline distinctions among players according to their category (age and level). This emphasises the importance of scrutinising these variables in athletes to comprehend their profiles and enable targeted interventions aimed at enhancing their psychological resources for competitive scenarios.